Practical binary analysis : build your own Linux tools for binary instrumentation, analysis, and disassembly - Andriesse, Dennis (No Starch Press, Inc., 2019)
"Begins with an introduction covering the basics of binary formats, disassembly, and code injection, then moves on to more advanced topics such as binary instrumentation, dynamic taint analysis, and symbolic execution"--